Academic Procrastination among Students with Dual Roles as Workers and Parents - Artikasari, Agustin Dewi; Affandi, Ghozali Rusyid (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
Academic procrastination is frequently observed among college students, especially those juggling multiple roles, including work and child-rearing. The demands of educational, professional, and familial duties can significantly hinder their capacity to finish assignments punctually. This study follows the Temporal Motivation Theory (Steel, 2007) and employs a unique case study methodology, focusing on two individuals from Universitas Muhammadiyah Sidoarjo (UMSIDA). The selection of participants was carried out using purposive and snowball sampling techniques. Data were gathered through semi-structured interviews and observations where the researchers did not take part, followed by analysis using the thematic approach outlined by Miles and Huberman. The results identify three primary reasons for procrastination: (1) a lack of belief in achieving success due to exhaustion, (2) a reduced perceived importance of academic tasks in comparison to work or family responsibilities, and; (3) a loose interpretation of deadlines. The study concludes that procrastination in academia acts as a way to cope with conflicting roles and helps in preserving mental balance